Highly efficient nonprecious metal catalyst prepared with metal-organic framework in a continuous carbon nanofibrous network - Shui, Jianglan; Chen, Chen; Grabstanowicz, Lauren; Zhao, Dan; Liu, Di-Jia (Proceedings of the National Academy of Sciences - PNAS, 2015)
Fuel cell vehicles, the only all-electric technology with a demonstrated >300 miles per fill travel range, use Pt as the electrode catalyst. The high price of Pt creates a major cost barrier for large-scale implementation of polymer electrolyte membrane fuel cells. Nonprecious metal catalysts (NPMCs) represent attractive low-cost alternatives. However, a significantly lower turnover frequency at the individual catalytic site renders the traditional carbon-supported NPMCs inadequate in reaching the desired performance afforded by Pt. Unconventional catalyst design aiming at maximizing the active site density at much improved mass and charge transports is essential for the next-generation NPMC. We report here a method of preparing highly efficient, nanofibrous NPMC for cathodic oxygen reduction reaction by electrospinning a polymer solution containing ferrous organometallics and zeolitic imidazolate framework followed by thermal activation. The catalyst offers a carbon nanonetwork architecture made of microporous nanofibers decorated by uniformly distributed high-density active sites. In a single-cell test, the membrane electrode containing such a catalyst delivered unprecedented volumetric activities of 3.3 A ⋅ cm(-3) at 0.9 V or 450 A ⋅ cm(-3) extrapolated at 0.8 V, representing the highest reported value in the literature. Improved fuel cell durability was also observed.